Lake water and talik groundwater interaction in continuous permafrost, Central Yakutia - Pavlova Nadezhda; Lebedeva Liudmila; Efremov Vladimir (E3S Web of Conferences, 2019)
Structural features of a lake talik associated with eolian relief are discussed. Analysis of hydrochemical and hydrological data for 2010-2017 showed that talik groundwater feeds lake and maintains perennial outflow from the lake. Variations in the chemical composition of the lake and outflowing creek are characterized on an annual and interannual basis. Seasonal comparison of hydrochemical data indicates a downward trend in dissolved-solids content of the lake water over the last six years, suggesting an increasing contribution of suprapermafrost groundwater to the lake and lake talik. Probable reason of enhanced suprapermafrost flow is increase of its duration due to observed rise of winter air temperature.